Arduino WIFI power switch appliances and motion sensor for energy saver / Muhammad Fakhrul Naim Nasarudin and Syed Muhammad Shahir Syed Hasan - Nasarudin, Muhammad Fakhrul Naim; Syed Hasan, Syed Muhammad Shahir (2019)
This report is describe the development of the low cost WIFI-power switch appliances and motion sensor for energy saver and safety using Arduino. Energy saver and safety is one of the crucial things nowadays. The demand of electricity has become higher than what electric company can supply. It make the price of electricity become higher. That’s why it is important to save energy as much as possible. Also, electric energy is dangerous for human body to take, therefore, it is crucial too to have a safety measures in everything that is connected to electric. In this project, WIFI module esp8266 esp-01 is used as a receiver that will receive signal from cloud server which is either to turn on the switch or turn off the switch without directly touch to the electric source. Other than that, motion sensor also being used in this project. This sensor will detect any motion and then turn the switch on. If there is no movement, the switch will turn off automatically. This will encourage more of energy saver. Commonly, a company need to spend a lot of money to cover their worker that get injured by electric shock and they also need to spend money on waste things such as electric that run without anyone using it. But with this device, a company could save their money and workers safety become more secure. This device can turn on or off switch from far which is more safe than directly touch from source and also, if there is no movement, the switch will not turn on which is will be as a backup plan if worker forget to close the switch before go back home from work. It will save energy and secure the worker safety. Thus, the objective of this project has been achieved.